Survival analysis and obstetric outcomes in patients with early stage ovarian cancer undergoing fertility-sparing surgery - Özer Birge; Mehmet Sait Bakır; Selen Doğan; Hasan Aykut Tuncer; Tayup Simsek (BMC, 2022)
Abstract Objective The aim of the present study is to evaluate the long-term outcomes in patients with early stage ovarian cancer undergoing fertility-sparing surgery. Methods The present study performed a retrospective analysis of recurrence, pregnancy and survival of a total of 66 patients who were diagnosed with early stage ovarian cancer (stage I) in XXX Faculty of Medicine Hospital between 2004 and 2019. Of these patients, 16 had undergone fertility-sparing surgery, and the remaining 50 patients had undergone radical surgery. Results Of 66 eligible patients, 16 had undergone fertility-sparing surgery, and the remaining 50 patients had undergone radical complete surgery. When demographic and descriptive data are taken into consideration, the mean age was 32.6 ± 6.76 years in patients undergoing fertility-sparing surgery and 54.05 ± 10.8 years in patients undergoing complete surgery, and the difference between the groups was statistically significant (p = 0.001). Of patients undergoing fertility-sparing surgery, 11 (16.7%) had stage Ia disease (most common), 5 (7.5%) had stage Ic disease, whereas no patient with stage Ib disease was detected. Of patients undergoing complete radical surgery, 32 (48.5%) had stage Ia disease (most common), 1 (1.5%) had stage Ib disease with bilateral ovarian involvement, and stage Ic was the second most common disease stage. Also, stage Ic3 was the most common disease stage (8 patients, 12.1%) among those with stage Ic disease. The rate of recurrence was 4.5% (3 patients) in patients undergoing fertility-sparing surgery, and recurrences occurred at 37 months, 69 months, and 76 months, respectively. A patient with stage Ic3 disease and endometrioid type tumor who developed recurrence at 37 months died at 130 months. Of patients undergoing complete surgery, ten patients (15.2%) developed recurrence, and there was no significant difference between the two groups in terms of recurrence (p = 1.00). At the end of 15-year follow-up period, there was no significant difference between patients undergoing fertility-preserving surgery and those undergoing complete surgery in terms of mortality (p = 0.668). Conclusion The observation of significant findings in terms of the rate of recurrence and disease-free survival following fertility-sparing surgery in patients with low-risk early stage ovarian cancer suggests that survival is positively affected in early stage ovarian cancer.